High-elasticity spraying film waterproof material as well as preparation method and application thereof

By adding specific ingredients to the waterproof material of acrylic spraying membrane, and the modification is performed, the elasticity and waterproof performance of the materials are improved, and the problem of difficulty to resist slight vibration and small cracks in existing materials has been solved. High elastic effect.

CN119331447APending Publication Date: 2025-01-21SICHUAN TONGSHEN WATERPROOF ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619607.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing acrylate sprayed waterproof materials are difficult to resist slight vibrations in buildings and cover small cracks, resulting in insufficient waterproofing performance.

Method used

Using high-elastic spraying membrane waterproof materials, its formula includes acrylic, methyl acrylic, N-hydroxyetylene acrylamide, N-hydroxymethylene, composite calcium carbonate, modified talcum powder, and modified silicon ash. Modification treatment improves the elasticity and waterproof performance of materials.

Benefits of technology

It realizes the excellent waterproof performance of not seeping at 120 minutes at 0.4MPa, and has high stretch strength and breakdown rate. It can effectively resist the slight vibration of the building and cover the small cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133097050000041
    Figure BDA0005133097050000041
  • Figure BDA0005133097050000121
    Figure BDA0005133097050000121
Patent Text Reader

Abstract

The invention relates to the technical field of building engineering materials, and discloses a high-elasticity spraying film waterproof material as well as a preparation method and application thereof. The high-elasticity spraying film waterproof material is prepared from the following raw materials in parts by mass: 140 to 160 parts of acrylic acid, 20 to 30 parts of methacrylic acid, 5 to 15 parts of N-hydroxyethyl acrylamide, 3 to 5 parts of N-hydroxymethyl acrylamide, 100 to 120 parts of composite calcium carbonate, 80 to 100 parts of modified talcum powder, 40 to 60 parts of modified silica fume, 3 to 5 parts of dispersing agent, 3 to 5 parts of defoaming agent and 290 to 310 parts of water. The high-elasticity spraying film waterproof material prepared by the preparation method disclosed by the invention is subjected to water seepage detection for 120min under 0.4 MPa, does not seep water and has excellent waterproof performance; the tensile strength of the prepared high-elasticity spraying film waterproof material can reach 1.9 MPa, the elongation at break can reach 305%, and the high-elasticity spraying film waterproof material has excellent elasticity, can resist slight vibration of buildings to a certain extent and can cover small cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building engineering materials, and in particular to a high-elastic spray film waterproof material and a preparation method and application thereof. Background Art

[0002] A large number of engineering practices have shown that water is a key factor affecting the safety, durability, stability and use of buildings; long-term rainwater erosion will cause steel bars to rust, reduce their strength and rigidity, and threaten personal safety. In order to avoid building leakage problems, waterproof and anti-seepage construction technology should be reasonably used in construction projects to improve the overall anti-seepage performance of building structures, extend their service life and avoid safety accidents.

[0003] Acrylate spray film waterproof material is a new type of polymer waterproof material with acrylate as the main component. It can quickly polymerize into a three-dimensional mesh structure within 1 to 5 seconds under the catalytic action of a curing agent, thereby achieving efficient waterproofing. With the continuous upgrading of some engineering requirements, people require that acrylate spray film waterproof materials can withstand slight vibrations of buildings to a certain extent and cover small cracks. Therefore, providing an acrylate spray film waterproof material with high elasticity has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0004] The purpose of the present invention is to provide a high-elastic spray film waterproof material and a preparation method and application thereof. The spray film waterproof material has high elasticity, can resist slight vibrations of buildings to a certain extent, and can cover small cracks.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A high-elastic spray film waterproof material comprises the following raw materials in parts by weight: 140-160 parts of acrylic acid, 20-30 parts of methacrylic acid, 5-15 parts of N-hydroxyethyl acrylamide, 3-5 parts of N-hydroxymethyl acrylamide, 100-120 parts of composite calcium carbonate, 80-100 parts of modified talc powder, 40-60 parts of modified silica fume, 3-5 parts of dispersant, 3-5 parts of defoamer and 290-310 parts of water.

[0008] Preferably, the high-elastic spray waterproof material comprises the following raw materials in parts by mass: 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of composite calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoaming agent and 300 parts of water.

[0009] Furthermore, the composite calcium carbonate is prepared by mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of (3-4):1.

[0010] Furthermore, the preparation method of the modified talcum powder comprises the following steps:

[0011] The talcum powder and the silane coupling agent are mixed and reacted to obtain the talcum powder modified by the silane coupling agent, namely the modified talcum powder.

[0012] Furthermore, the mass ratio of the talc powder to the silane coupling agent is 1:(1.5-2.5).

[0013] Furthermore, the reaction is specifically: reacting at 120-160° C. for 40-80 min.

[0014] Furthermore, the preparation method of the modified silica fume comprises the following steps:

[0015] 1) Mixing silica fume and H2SO4 solution, impregnating and modifying, and obtaining oxidized modified silica fume;

[0016] 2) The oxidized modified silica fume obtained in step 1) is mixed with a silane coupling agent and reacted to obtain silica fume modified with a silane coupling agent, namely, the modified silica fume.

[0017] Furthermore, in step 1), the H2SO4 solution is a H2SO4 solution with a volume fraction of 70%.

[0018] Furthermore, in step 1), the mass volume ratio of the silica ash and the H2SO4 solution is 1g: (2-4)mL.

[0019] Furthermore, in step 1), the impregnation modification is specifically: impregnation modification for 20 to 40 minutes.

[0020] Furthermore, in step 1), after the impregnation modification, filtration is required, alkali washing is performed to neutrality, and drying is performed.

[0021] Furthermore, in step 2), the mass ratio of the oxidatively modified silica fume to the silane coupling agent is 1:(1.5-2.5).

[0022] Furthermore, in step 2), the reaction is specifically: reacting at 60-100° C. for 90-120 min.

[0023] The second technical solution of the present invention:

[0024] The method for preparing the above-mentioned high elastic spray film waterproof material comprises the following steps:

[0025] Acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide are added to water and mixed, then a dispersant and a defoamer are added and mixed, and finally composite calcium carbonate, modified talcum powder and modified silica fume are added and mixed to obtain the high elastic spray film waterproof material.

[0026] The third technical solution of the present invention:

[0027] The application of the above-mentioned high elastic spray film waterproof material in waterproofing projects.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The high elastic spray film waterproof material prepared by the present invention is tested for water seepage at 0.4 MPa for 120 minutes and is water-free, thus having excellent waterproof performance.

[0030] The high-elastic spray film waterproof material prepared by the present invention has a tensile strength of up to 1.9 MPa and an elongation at break of up to 305%. It has excellent elasticity, can resist slight vibrations of buildings to a certain extent, and can cover small cracks. DETAILED DESCRIPTION

[0031] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0032] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0036] In the following examples, all the raw materials used are commercially available, as shown in Table 1;

[0037] Table 1 Raw materials and specifications

[0038]

[0039] In the following embodiment, a method for preparing a high elastic spray film waterproof material comprises the following steps:

[0040] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of (3-4):1 to obtain composite calcium carbonate;

[0041] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:(1.5-2.5), reacting at 120-160° C. for 40-80 min, to obtain talc modified with silane coupling agent, i.e., modified talc;

[0042] 3) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g: (2-4)mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, and the mixture is impregnated for 20-40min, filtered, washed with alkali until neutral, and dried to obtain oxidized modified silica fume;

[0043] 4) mixing the oxidized modified silica fume obtained in step 3) with the silane coupling agent in a mass ratio of 1:(1.5-2.5), reacting at 60-100° C. for 90-120 min to obtain silica fume modified with a silane coupling agent, i.e., modified silica fume;

[0044] 5) Weigh each raw material according to the following mass parts:

[0045] 140-160 parts of acrylic acid, 20-30 parts of methacrylic acid, 5-15 parts of N-hydroxyethyl acrylamide, 3-5 parts of N-hydroxymethyl acrylamide, 100-120 parts of composite calcium carbonate, 80-100 parts of modified talc, 40-60 parts of modified silica fume, 3-5 parts of dispersant, 3-5 parts of defoamer and 290-310 parts of water;

[0046] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 5) are added to the water weighed in step 5), stirred for 1 hour, then the dispersant and defoamer weighed in step 5) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 5) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0047] In the following examples and comparative examples, the silane coupling agent used is silane coupling agent KH-560.

[0048] Example 1

[0049] A high elastic spray film waterproof material

[0050] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 3:1 to obtain composite calcium carbonate;

[0051] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:1.5, reacting at 120° C. for 40 min to obtain talc modified with silane coupling agent, i.e., modified talc;

[0052] 3) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:2mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, and the mixture is impregnated for 20 to 40 minutes, filtered, washed with alkali until neutral, and dried to obtain oxidized modified silica fume;

[0053] 4) mixing the oxidized modified silica fume obtained in step 3) with the silane coupling agent in a mass ratio of 1:1.5, and reacting at 60° C. for 90 min to obtain silica fume modified with the silane coupling agent, i.e., modified silica fume;

[0054] 5) Weigh each raw material according to the following mass parts:

[0055] 140 parts of acrylic acid, 20 parts of methacrylic acid, 5 parts of N-hydroxyethyl acrylamide, 3 parts of N-hydroxymethyl acrylamide, 100 parts of composite calcium carbonate, 80 parts of modified talc, 40 parts of modified silica fume, 3 parts of dispersant, 3 parts of defoamer and 290 parts of water;

[0056] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 5) are added to the water weighed in step 5), stirred for 1 hour, then the dispersant and defoamer weighed in step 5) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 5) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0057] Example 2

[0058] A high elastic spray film waterproof material

[0059] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 3.5:1 to obtain composite calcium carbonate;

[0060] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:2, reacting at 140° C. for 60 min to obtain talc modified with silane coupling agent, i.e., modified talc;

[0061] 3) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:3mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, impregnated for 30min, filtered, washed with alkali to neutrality, and dried to obtain oxidized modified silica fume;

[0062] 4) mixing the oxidized modified silica fume obtained in step 3) with the silane coupling agent in a mass ratio of 1:2, and reacting at 80° C. for 100 min to obtain silica fume modified with the silane coupling agent, i.e., modified silica fume;

[0063] 5) Weigh each raw material according to the following mass parts:

[0064] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of composite calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0065] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 5) are added to the water weighed in step 5), stirred for 1 hour, then the dispersant and defoamer weighed in step 5) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 5) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0066] Example 3

[0067] A high elastic spray film waterproof material

[0068] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 4:1 to obtain composite calcium carbonate;

[0069] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:2.5, reacting at 160° C. for 80 min to obtain talc modified with silane coupling agent, i.e., modified talc;

[0070] 3) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:4mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, impregnated for 40min, filtered, washed with alkali to neutrality, and dried to obtain oxidized modified silica fume;

[0071] 4) mixing the oxidized modified silica fume obtained in step 3) with the silane coupling agent in a mass ratio of 1:2.5, and reacting at 100° C. for 120 min to obtain silica fume modified with a silane coupling agent, i.e., modified silica fume;

[0072] 5) Weigh each raw material according to the following mass parts:

[0073] 160 parts of acrylic acid, 30 parts of methacrylic acid, 15 parts of N-hydroxyethyl acrylamide, 5 parts of N-hydroxymethyl acrylamide, 120 parts of composite calcium carbonate, 100 parts of modified talc, 60 parts of modified silica fume, 5 parts of dispersant, 5 parts of defoamer and 310 parts of water;

[0074] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 5) are added to the water weighed in step 5), stirred for 1 hour, then the dispersant and defoamer weighed in step 5) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 5) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0075] Comparative Example 1

[0076] A spray film waterproof material

[0077] 1) mixing talc and a silane coupling agent in a mass ratio of talc to a silane coupling agent of 1:2, and reacting at 140° C. for 60 min to obtain talc modified with a silane coupling agent, i.e., modified talc;

[0078] 2) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:3mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, impregnated for 30min, filtered, washed with alkali to neutrality, and dried to obtain oxidized modified silica fume;

[0079] 3) mixing the oxidized modified silica fume obtained in step 2) with the silane coupling agent in a mass ratio of 1:2, and reacting at 80° C. for 100 min to obtain silica fume modified with the silane coupling agent, i.e., modified silica fume;

[0080] 4) Weigh each raw material according to the following mass parts:

[0081] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of heavy calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0082] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 4) are added to the water weighed in step 4), stirred for 1 hour, then the dispersant and defoamer weighed in step 4) are added, stirred for 30 minutes, and finally the heavy calcium carbonate, modified talcum powder and modified silica fume weighed in step 4) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0083] Comparative Example 2

[0084] A spray film waterproof material

[0085] 1) mixing talc and a silane coupling agent in a mass ratio of talc to a silane coupling agent of 1:2, and reacting at 140° C. for 60 min to obtain talc modified with a silane coupling agent, i.e., modified talc;

[0086] 2) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:3mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, impregnated for 30min, filtered, washed with alkali to neutrality, and dried to obtain oxidized modified silica fume;

[0087] 3) mixing the oxidized modified silica fume obtained in step 2) with the silane coupling agent in a mass ratio of 1:2, and reacting at 80° C. for 100 min to obtain silica fume modified with the silane coupling agent, i.e., modified silica fume;

[0088] 4) Weigh each raw material according to the following mass parts:

[0089] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of light calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0090] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 4) are added to the water weighed in step 4), stirred for 1 hour, then the dispersant and defoamer weighed in step 4) are added, stirred for 30 minutes, and finally the light calcium carbonate, modified talcum powder and modified silica fume weighed in step 4) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0091] Comparative Example 3

[0092] A spray film waterproof material

[0093] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 3.5:1 to obtain composite calcium carbonate;

[0094] 2) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:3mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, impregnated for 30min, filtered, washed with alkali to neutrality, and dried to obtain oxidized modified silica fume;

[0095] 3) mixing the oxidized modified silica fume obtained in step 2) with the silane coupling agent in a mass ratio of 1:2, and reacting at 80° C. for 100 min to obtain silica fume modified with the silane coupling agent, i.e., modified silica fume;

[0096] 4) Weigh each raw material according to the following mass parts:

[0097] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of composite calcium carbonate, 90 parts of talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0098] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 4) are added to the water weighed in step 4) and stirred for 1 hour, then the dispersant and defoamer weighed in step 4) are added and stirred for 30 minutes, and finally the composite calcium carbonate, talcum powder and modified silica fume weighed in step 4) are added and stirred for 40 minutes to obtain the high elastic spray film waterproof material.

[0099] Comparative Example 4

[0100] A spray film waterproof material

[0101] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 3.5:1 to obtain composite calcium carbonate;

[0102] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:2, reacting at 140° C. for 60 min to obtain talc modified with silane coupling agent, i.e., modified talc;

[0103] 3) mixing silica fume and silane coupling agent in a mass ratio of 1:2, reacting at 80° C. for 100 min to obtain silica fume modified by silane coupling agent, i.e., modified silica fume;

[0104] 4) Weigh each raw material according to the following mass parts:

[0105] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of composite calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0106] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 4) are added to the water weighed in step 4), stirred for 1 hour, then the dispersant and defoamer weighed in step 4) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 4) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0107] Comparative Example 5

[0108] A spray film waterproof material

[0109] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 3.5:1 to obtain composite calcium carbonate;

[0110] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:2, reacting at 140° C. for 60 min to obtain talc modified with silane coupling agent, i.e., modified talc;

[0111] 3) According to the mass volume ratio of silica fume to H2O2 solution with a volume fraction of 30% of 1g:3mL, silica fume is mixed with H2O2 solution with a volume fraction of 30%, impregnated for 30min, filtered, washed, and dried to obtain oxidatively modified silica fume;

[0112] 4) mixing the oxidized modified silica fume obtained in step 3) with the silane coupling agent in a mass ratio of 1:2, and reacting at 80° C. for 100 min to obtain silica fume modified with the silane coupling agent, i.e., modified silica fume;

[0113] 5) Weigh each raw material according to the following mass parts:

[0114] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of composite calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0115] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 5) are added to the water weighed in step 5), stirred for 1 hour, then the dispersant and defoamer weighed in step 5) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 5) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0116] Comparative Example 6

[0117] A spray film waterproof material

[0118] 1) mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of 3.5:1 to obtain composite calcium carbonate;

[0119] 2) mixing talc and silane coupling agent in a mass ratio of talc to silane coupling agent of 1:2, reacting at 140° C. for 60 min to obtain talc modified with silane coupling agent, i.e., modified talc;

[0120] 3) According to the mass volume ratio of silica fume to H2SO4 solution with a volume fraction of 70% of 1g:3mL, silica fume is mixed with H2SO4 solution with a volume fraction of 70%, impregnated for 30min, filtered, washed with alkali to neutrality, and dried to obtain oxidized modified silica fume, i.e. modified silica fume;

[0121] 4) Weigh each raw material according to the following mass parts:

[0122] 150 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 4 parts of N-hydroxymethyl acrylamide, 110 parts of composite calcium carbonate, 90 parts of modified talc, 50 parts of modified silica fume, 4 parts of dispersant, 4 parts of defoamer and 300 parts of water;

[0123] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide weighed in step 4) are added to the water weighed in step 4), stirred for 1 hour, then the dispersant and defoamer weighed in step 4) are added, stirred for 30 minutes, and finally the composite calcium carbonate, modified talcum powder and modified silica fume weighed in step 4) are added, stirred for 40 minutes, to obtain the high elastic spray film waterproof material.

[0124] Effect verification

[0125] Referring to Q / CR 517.1-2017, the mechanical properties of the sprayed waterproof materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were tested. The results of the mechanical properties test are shown in Table 2.

[0126] Table 2 Mechanical properties test results

[0127]

[0128] It can be seen from the data in Table 2 that the high elastic spray film waterproof material prepared by the present invention is water-proof in the water seepage test under 0.4 MPa for 120 min, and has excellent waterproof performance;

[0129] It can be seen from the data in Table 2 that the high-elastic spray waterproof material prepared by the present invention has a tensile strength of up to 1.9 MPa and an elongation at break of up to 305%, has excellent elasticity, can withstand slight vibrations of buildings to a certain extent, and can cover small cracks; and it can be seen from Comparative Examples 1 to 6 that omitting the addition of light calcium carbonate, omitting the addition of heavy calcium carbonate, omitting the modification of talcum powder, omitting the oxidation modification of silica fume, changing the oxidation modifier of silica fume, and omitting the silane coupling agent modification of silica fume will all reduce the elasticity of the spray waterproof material to a certain extent.

[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high elastic spray film waterproof material, characterized in that: The invention comprises the following raw materials in parts by weight: 140-160 parts of acrylic acid, 20-30 parts of methacrylic acid, 5-15 parts of N-hydroxyethyl acrylamide, 3-5 parts of N-hydroxymethyl acrylamide, 100-120 parts of composite calcium carbonate, 80-100 parts of modified talc powder, 40-60 parts of modified silica fume, 3-5 parts of dispersant, 3-5 parts of defoaming agent and 290-310 parts of water.

2. A high elastic spray film waterproof material according to claim 1, characterized in that: The composite calcium carbonate is prepared by mixing heavy calcium carbonate and light calcium carbonate in a mass ratio of (3-4):

1.

3. The high elastic spray film waterproof material according to claim 1, characterized in that: The preparation method of the modified talcum powder comprises the following steps: The talcum powder and the silane coupling agent are mixed and reacted to obtain the talcum powder modified by the silane coupling agent, namely the modified talcum powder.

4. A high elastic spray film waterproof material according to claim 3, characterized in that: The mass ratio of the talc powder to the silane coupling agent is 1:(1.5-2.5); the reaction is specifically: reacting at 120-160° C. for 40-80 minutes.

5. The high elastic spray film waterproof material according to claim 1, characterized in that: The preparation method of the modified silica fume comprises the following steps: 1) Mixing silica fume and H2SO4 solution, impregnating and modifying, and obtaining oxidized modified silica fume; 2) The oxidized modified silica fume obtained in step 1) is mixed with a silane coupling agent and reacted to obtain silica fume modified with a silane coupling agent, namely, the modified silica fume.

6. The high elastic spray film waterproof material according to claim 5, characterized in that: In step 1), the H2SO4 solution is a H2SO4 solution with a volume fraction of 70%; the mass volume ratio of the silica ash and the H2SO4 solution is 1g: (2-4)mL; the impregnation modification is specifically: impregnation modification for 20-40min.

7. The high elastic spray film waterproof material according to claim 5, characterized in that: In step 2), the mass ratio of the oxidatively modified silica fume to the silane coupling agent is 1:(1.5-2.5); the reaction is specifically: reacting at 60-100° C. for 90-120 min.

8. A method for preparing the high elastic spray film waterproof material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and N-hydroxymethyl acrylamide are added to water and mixed, then a dispersant and a defoamer are added and mixed, and finally composite calcium carbonate, modified talcum powder and modified silica fume are added and mixed to obtain the high elastic spray film waterproof material.

9. Use of the high elastic spray film waterproof material as claimed in any one of claims 1 to 7 in waterproofing projects.